Accessing γ-Ga2S3 by solventless thermolysis of gallium xanthates: a low-temperature limit for crystalline products. Issue 41 (7th August 2019) - Alderhami, Suliman A.; Collison, David; Lewis, David J.; McNaughter, Paul D.; O'Brien, Paul; Spencer, Ben F.; Vitorica-Yrezabal, Inigo; Whitehead, George
Abstract : Alkyl-xanthato gallium(iii ) complexes, [Ga(S2 COR)3 ] where R = Me, Et, i Pr, n Pr, n Bu, s Bu and i Bu, have been synthesized and examined as potential precursors for gallium sulfides. Abstract : Alkyl–xanthato gallium(iii ) complexes of the form [Ga(S2 COR)3 ], where R = Me (1 ), Et (2 ), i Pr (3 ), n Pr (4 ), n Bu (5 ), s Bu (6 ) and i Bu (7 ), have been synthesized and fully characterised. The crystal structures for 1 and 3–7 have been solved and examined to elucidate if these structures are related to their decomposition. Thermogravimetric analysis was used to gain insight into the decomposition temperatures for each complex. Unlike previously explored metal xanthate complexes which break down at low temperatures (<250 °C), to form crystalline metal chalcogenides, powder X-ray diffraction measurements suggest that when R ≥ Et these complexes did not produce crystalline gallium sulfides until heated to 500 °C, where γ-Ga2 S3 was the sole product formed. In the case of R = Me, Chugaev elimination did not occur and amorphous Ga x S y products were formed. We conclude therefore that the low-temperature synthesis route offered by the thermal decomposition of metal xanthate precursors, which has been reported for many metal sulfide systems prior to this, may not be appropriate in the case of gallium sulfides.